2011
DOI: 10.3174/ajnr.a2481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Readout-Segmented− Echo-Planar Imaging for Diffusion-Weighted Imaging in Pediatric Brain

Abstract: BACKGROUND AND PURPOSE RS-EPI has been suggested as an alternative approach to EPI for high-resolution DWI with reduced distortions. To determine whether RS-EPI is a useful approach for routine clinical use, we implemented GRAPPA-accelerated RS-EPI DWI at our pediatric hospital and graded the images alongside standard accelerated (ASSET) EPI DWI used routinely for clinical studies. MATERIALS AND METHODS GRAPPA-accelerated RS-EPI DWIs and ASSET EPI DWIs were acquired on 35 pediatric patients using a 3T system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 10 publications
7
51
0
Order By: Relevance
“…This method provides images with less artefacts and higher resolution for the evaluation of brain, brain stem and the breast [11][12][13]. However, to the best of our knowledge, its effectiveness in the evaluation of middle-ear cholesteatoma has not been established, yet.…”
Section: Introductionmentioning
confidence: 99%
“…This method provides images with less artefacts and higher resolution for the evaluation of brain, brain stem and the breast [11][12][13]. However, to the best of our knowledge, its effectiveness in the evaluation of middle-ear cholesteatoma has not been established, yet.…”
Section: Introductionmentioning
confidence: 99%
“…Segmented EPI (MS-DWI) techniques have been investigated primarily in brain imaging [18,19], although applicability in other organs has been studied as well [20–22]. Recently, Thian et al [23] studied the feasibility and image quality of MS-DWI in the pelvis in a mixed cohort of male and female patients.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a left/right mirror image is formed along the frequency-encoding direction, but each echo has a different phase encode on the phase-encoding direction by phase-encoded blips. 2,[15][16][17] Interference RF signals occurring at the same frequency range symmetrically fill in the two sides of the centre frequency and form multiple parallel symmetrical linear stippled or dashed bands in the phaseencoding direction. Our study suggested that the gaps of RF artefacts were mainly affected by different BWs, and our results supported that RF artefact could be gradually moved away from the centre of the image by decreasing the BW within a suitable range.…”
Section: Discussionmentioning
confidence: 99%